The CO2 electrolysing mechanism in single-phase mixed-conducting cathode of solid oxide cell - Zidi Zhu; Yunan Jiang; Yunan Jiang; Lijie Zhang; Hairui Han; Aijun Li; Changrong Xia; Changrong Xia (Frontiers in Chemistry, 2024)
In the field of solid oxide cells (SOC), unveiling the electrochemical reaction and transfer mechanisms in mixed ionic and electronic conducting (MIEC) electrodes is of great importance. Due to the chemical capacitance effects of MIEC materials, SOC often shows large capacitance current during electrochemical tests, which might interfere with the polarization behaviors. This work presents a numerical multiphysical model based on the transport of oxygen species, which accurately and concisely replicates the current-voltage curves of a solid oxide electrolysis cell (SOEC) with MIEC electrodes under various scanning rates. The scanning IV and electrochemical impedance spectra measurement under different SOEC working conditions are combined to enable the separation of Faradic and charging currents. Thus, both the bulk diffusion and surface gaseous diffusion of the oxygen species are encompassed, which explains how the current being generated due to intertwined chemical capacitance effects and chemical reactions in the MIEC electrodes.